2017
DOI: 10.1080/21655979.2016.1267883
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of microbial fuel cell (MFC) using suitable electrode and Bioengineered organisms: A review

Abstract: There is an urgent need to find an environment friendly and sustainable technology for alternative energy due to rapid depletion of fossil fuel and industrialization. Microbial Fuel Cells (MFCs) have operational and functional advantages over the current technologies for energy generation from organic matter as it directly converts electricity from substrate at ambient temperature. However, MFCs are still unsuitable for high energy demands due to practical limitations. The overall performance of an MFC depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 80 publications
1
53
0
1
Order By: Relevance
“…Numerous research studies are being conducted to evaluate the influence of the electrode materials on the performance and cost of the MFCs. Carbon materials, which are noncorrosive, have been widely used because of their high electrical conductivity and chemical stability, e.g., carbon rod, carbon fiber, carbon felt, and carbon cloth [3]. Biocompatibility, specific surface area, electrical conductivity, and cost are important factors for its selection.…”
Section: Basic Components Of Dual-chambered Mfcs Using a Mediatormentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous research studies are being conducted to evaluate the influence of the electrode materials on the performance and cost of the MFCs. Carbon materials, which are noncorrosive, have been widely used because of their high electrical conductivity and chemical stability, e.g., carbon rod, carbon fiber, carbon felt, and carbon cloth [3]. Biocompatibility, specific surface area, electrical conductivity, and cost are important factors for its selection.…”
Section: Basic Components Of Dual-chambered Mfcs Using a Mediatormentioning
confidence: 99%
“…Therefore, metals are problematic to use, except for stainless and titanium. To improve such problem, materials in which metal is incorporated into graphite have been made [3].…”
Section: Basic Components Of Dual-chambered Mfcs Using a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last years, much research efforts have focused on the optimization of the microbe/electrode interface in order to boost the power output of MET via (i) engineering the structure and chemistry of the electrode and (ii) tailoring the biofilm structure/composition …”
Section: Introductionmentioning
confidence: 99%
“…19 Over the last years, much research efforts have focused on the optimization of the microbe/electrode interface in order to boost the power output of MET via (i) engineering the structure and chemistry of the electrode and (ii) tailoring the biofilm structure/composition. [20][21][22][23] As an example, a recent study 24 demonstrated the possibility to improve power generation by Shewanella PV-4 in a microbial fuel cell (MFC), by exploiting biogenic iron sulfide nanoparticles (NPs), capable of facilitating extracellular electron transfer reactions between microbes and the electrode. Studies designed to address the fundamental mechanisms of charge transport in this system showed that charge transport occurred only in the presence of live Shewanella, and moreover demonstrated that the enhanced current output could be attributed to improved electron transfer at the cell/electrode interface and through the cellular networks.…”
Section: Introductionmentioning
confidence: 99%